Discoveries in Transforming Student Engagement through Full-Day School Learning Motivation Research: Penemuan dalam Mengubah Keterlibatan Siswa melalui Penelitian Motivasi Belajar Sekolah Sehari Penuh - Azizah, Siti Hidayatul; Widyastuti, Widyastuti (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the learning motivation levels among high-grade students at SD Islam Sabilillah Sidoarjo, utilizing a descriptive quantitative research approach with a sample size of 217 out of a total population of 506 students. Data analysis via descriptive statistical tests revealed that 68% of students demonstrated a moderate level of learning motivation, while 19% exhibited a high level and 13% had a low level. These findings highlight the students' ability to sustain learning motivation during academic activities at school and offer insights for enhancing motivation strategies in full-day school settings, with implications for educational institutions and policymakers. Highlight: Quantitative assessment of learning motivation in full-day school students. Representative sample selection via proportionate stratified random sampling. Insights for educational strategies and improved student engagement outcomes. Keyword: Learning Motivation, Full-Day School, Student Engagement, Descriptive Quantitative Research, Educational Strategies